2022
DOI: 10.1093/mnras/stac1810
|View full text |Cite
|
Sign up to set email alerts
|

The bulge masses of TDE host galaxies and their scaling with black hole mass

Abstract: Tidal disruption events (TDEs) provide a means to probe the low end of the supermassive black hole (SMBH) mass distribution, as they are only observable below the Hills mass (≲ 108M⊙). Here we attempt to calibrate the scaling of SMBH mass with host galaxy bulge mass, enabling SMBH masses to be estimated for large TDE samples without the need for follow-up observations or extrapolations of relations based on high-mass samples. We derive host galaxy masses using prospector fits to the UV-MIR spectral energy dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…A fraction of our TDE host galaxies have been analyzed with similar approaches in the literature (Ramsden et al 2022;Hammerstein et al 2023). In Appendix C, we show that our estimates of M gal and 0,0 u − r are mostly consistent with previous results, and point out possible reasons for the differences.…”
Section: Sed Fittingsupporting
confidence: 86%
“…A fraction of our TDE host galaxies have been analyzed with similar approaches in the literature (Ramsden et al 2022;Hammerstein et al 2023). In Appendix C, we show that our estimates of M gal and 0,0 u − r are mostly consistent with previous results, and point out possible reasons for the differences.…”
Section: Sed Fittingsupporting
confidence: 86%
“…Our use of total galaxy mass instead of bulge mass may be the source of the discrepancy. While Ramsden et al (2022) derive the host galaxy masses in a similar manner to the one presented here and are generally consistent with those in Table 2, they perform bulge-disk decompositions on SDSS and Pan-STARRS imaging of the TDE hosts. Hammerstein et al (2021) note that imaging from ground-based observatories may not provide the resolution required to study galaxy morphology at the redshifts of the TDE hosts.…”
Section: Mosfitmentioning
confidence: 59%
“…Furthermore, this is in conflict with Mockler et al (2019), who found that their estimates of the black hole mass are consistent with the estimates from the bulk galaxy properties. We point out that two joint papers that were released shortly before the submission of this manuscript, Nicholl et al (2022) and Ramsden et al (2022), find a positive correlation between black hole mass measured from MOSFiT and host galaxy bulge mass measured from stellar population synthesis fitting. Our use of total galaxy mass instead of bulge mass may be the source of the discrepancy.…”
Section: Mosfitmentioning
confidence: 84%
“…Moreover, (iii) X-rays from all of the neutrinoassociated sources have been detected, although X-ray detection is generally rare in TDEs (see, e.g., van Velzen et al 2021b). In all cases, (iv) the estimated SMBH masses (with large uncertainties) are between about 10 6.5 and 10 7.5 M e (van Velzen et al 2021a), with two of them being higher than the mean of the observed population (M M 10 6.57   ; see Nicholl et al 2022;Ramsden et al 2022). Consequently, all events should have correspondingly high BB luminosities as a consequence of high Eddington luminosities-for which the measured values in the OUV range are only lower limits, due to obscuration effects.…”
Section: Introductionmentioning
confidence: 99%